Radiotherapy for small cell lung cancer in current clinical practice guidelines - Haiyan Zeng; Dirk K.M. De Ruysscher; Xiao Hu; Danyang Zheng; Li Yang; Umberto Ricardi; Feng-Ming Spring Kong; Lizza E.L. Hendriks (Journal of the National Cancer Center, 2022)
Several guidelines including radiotherapy recommendations exist worldwide for the treatment of small cell lung cancer (SCLC). To evaluate the differences in radiotherapy recommendations we conducted a systematic review. PubMed and the sites of medical societies were searched for SCLC guidelines published in either English, Chinese, or Dutch. This was limited to January 2018 till February 2021 to only include up-to-date recommendations. Data was extracted and compared regarding the guideline's development method and radiotherapy recommendations. Eleven guidelines were identified (PubMed n=4, societies n=7) from Spain (n=1), Canada (n=1), America (n=3), United Kingdom (n=1), the Netherlands (n=1), and China (n=3), respectively. Nine guidelines assessed the strength of evidence (SOE) and specified the strength of recommendation (SOR), although methods were different. The major radiotherapy recommendations are similar although differences exist in thoracic radiotherapy (TRT) dose, time, and volume. Controversial areas are TRT in resected stage I-IIA (pN1), prophylactic cranial irradiation (PCI) in resected as well as unresected stage I-IIA, stereotactic body radiation therapy (SBRT) in unresected stage I-IIA, PCI time, and PCI versus magnetic resonance imaging (MRI) surveillance in stage IV. The existence of several overlapping guidelines for SCLC treatment indicates that guideline development is (unnecessarily) repeated by different organizations or societies. Improvement could be made by better international collaboration to avoid duplicating unnecessary work, which would spare a lot of time and resources. Efforts should be made to work together on controversial or unknown fields.